(untitled) (The Review of Diabetic Studies, 2025)
INTRODUCTION : Biofeedback enables the individual to increase awareness and it helps to refine movement sequence. This study involves the use of visual biofeedback with laser pointer for improving eye hand coordination in Parkinson disease patients .parkinson disease is manifested by many cardinal features and one of the most common feature is lack of ye hand coordination . parkinson disease patients unlike normal subjects were unable to maintain normal trunk alignment without visual orientation. Hence treating eye hand coordination is essential for healthy living of Parkinson disease patients . METHODS : . It is an observational study design. 20 subjects were screened and 10 subjects were selected based on the inclusion and exclusion criteria. The study setting was at OP Department of Physiotherapy.Parameter used to test eye hand coordination is finger to nose test . Inclusion criteria includes male parkinson disease patients of age group 60- 80years, patients with intact visual and auditory sensation , patients with eye hand coordination score greater than 2, patients without any other neurological disorders, patients without balance disorders. Exclusion criteria includes patients with age group less than 50 and those with neurological disorders, patients with lack of visual and auditory response.The study duration is about 10 weeks and treatment duration is 6 weeks .The method of intervention applied was laser pointer visual biofeedback training with hand and forehead pointer . RESULTS : The eye hand coordination is assessed using finger to nose test. Based on pretest and postest analysis , the application of laser pointer visual biofeedback training is found to be statistically significant. The pretest and posttest mean are 3.44 and 1.78. The pretest and post test standard deviation are 0.73 and 0.67. The calculated t value is 5.96 and table t value is 2.306. As the calculated t value is greater than table t value , the result was statistically significant. DISCUSSION : The laser pointer provides immediate visual cues, helping brain synchronize sensory input ( visual tracking ) with motor output. Repeated practice strengthens neural pathways responsible for eye – hand coordination , improving precision and reaction time. By connecting visual input (the laser dot) with motor output (neck and eye movement), it enhances the ability to integrate these two systems, a key component of eye-hand coordination.